The racketeer - Grisham, John. (New York : Doubleday, 2012)
The Racketeer follows the murder of Federal Judge Raymond Fogletree. His body and his secretarys body were found in a lakeside cabin with an empty safe. Malcolm Bannister, a former lawyer, currently in prison, knows who did the killing and why. He's willing to tell, for a price.
Keywords: Judges -- Fiction; Mystery fiction